Prevalence of airflow obstruction according GOLD, ATS and ERS criteria in symptomatic ever-smokers referring to a Pulmonary Rehabilitation Department - Barbarito, N.; Vaghi, A.; De Mattia, E. (Monaldi Archives for Chest Disease, 2015)
Aim. To evaluate in a Pulmonary Rehabilitation (PR) setting the prevalence of airflow obstruction (AO) in either current or former smokers â‰¥45 years old both with dyspnoea and with chronic productive cough, using European Respiratory society (ERS) statement (FEV1/SVC <88 and <89% predicted in men and women, respectively), American Thoracic Society (ATS) statement (FEV1/FVC <75%), and Global Initiative for Chronic Obstructive Lung Disease (GOLD) statement (FEV1/FVC <70%). Methods. Lung function tests were performed in each patient who was referred to our PR department due to respiratory diagnosis or symptoms. For analysis, in patients showing AO we used post-bronchodilator lung function values. Results. In 184 ever-smoker patients with symptoms of chronic obstructive pulmonary disease (COPD), the prevalence rates of AO were as follows: ERS = 89.7%, ATS = 76.6%, and GOLD = 63.6%. Patients with AO according ERS criteria showing moderate to severe (M/S) obstruction (i.e., FEV1 <70% predicted) were 119. Patients with ERS M/S AO but without AO using either ATS or GOLD criteria were 8.4% and 19.3%, respectively. Conclusions. Prevalence of AO is highly dependent on which guidelines it is based. ATS and particularly GOLD statement can cause a large under-diagnosis even of moderate to severe COPD. Diagnosis of COPD may be overlooked if SVC is not performed.